Drink, death, and driving: Do blood alcohol content limit reductions improve road safety?. (13th March 2020) - Cooper, Benjamin; Gehrsitz, Markus; McIntyre, Stuart G.
Abstract: This study exploits a natural experiment in Scotland where the legal blood alcohol content (BAC) limit was reduced from 0.8 to 0.5 mg per 100 ml of blood while staying constant in all other parts of the United Kingdom. Using a difference‐in‐differences design, we find that this change in the BAC level had no impact on either traffic accident or fatality rates.